رسول اللہ ﷺ کے مشروبات اقسام اور طبی فوائد کا تحقیقی مطالعہ: Exploring the Beverages Recommended by the Messenger of Allah (PBUH): A Research Inquiry into Types and Medicinal Properties - Dr Saeed Ahmad Saeedi; Muhammad Haris Ali (International Research Journal of Arabic and Islamic Studies, 2024)
Allah Almighty created humans and also provided them with the necessities, especially natural remedies to alleviate their ailments. Prophets are the sources of divine guidance and his blessings. Therefore, unlike physicians, who rely on their experience and observations to recommend remedies, prophets only rely on the guidance of Almighty Allah. The article delves into the study of the favorite drinks of the holy Prophet that are recommended by him. The significance of the article lies in the fact that it delves into the bibliographical accounts of the Holy Prophet discussed in the books of Sirah and Hadith to find out his favorite drinks and their benefits in the context of the contemporary age. The Holy Prophet (PBUH) had a variety of favorite drinks, including honey, milk, raisin water, Zamzam water, sweetened cold water, raw lassi, olive oil, Satu Water, vinegar, and Talbinah. He emphasized the unique benefits of each drink and highlighted their importance for overall health and well-being. For instance, raisin water, the Prophet's favorite drink, is beneficial for nervous energy and external beauty. Zamzam water, which the Prophet (PBUH) loved, is a refreshing drink and a sign of faith. Similarly, the Holy Prophet (PBUH) himself informed us that the creation of honey is a great masterpiece of the Creator's power and has various benefits for various ailments as is proved by modern sciences. Milk is also the favorite drink of the Holy Prophet, and it has its unique benefits. Likewise, sweet cold water is the Prophet's favorite drink, and the benefits of water cannot be overstated given that the survival of the human race is not possible without it. However, while considering the manners of drinking water, as taught by the Prophet (PBUH), will reap its benefits. This exploration of the Prophet's favorite drinks underscores their enduring relevance in contemporary society, offering profound insights into integrating physical health and spiritual nourishment within Islamic teachings.